Education Information Systems Planning Practices and Performance of Government Agencies in Malaysia - Rahmat, Abdul; Harun, Hisyam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
The relevance and applicability of Strategic information systems planning (SISP) to both private and public organizations have been emphasized in someliteratures. However, the literature review indicates that there are not many studies that have attempted to examine the correlationbetween SISP practices and performance of organizations in the public sector. In an attempt to address this issue, this study examined the correlationbetween SISP practices and performance of government agencies. The data for the study werecollectedfrom 54 government agencies in Malaysia that adopted the SISP. Thedata analysis was done in severalstagesof analysisthat includesa)descriptive analysis, consistedofmean, median, standard deviation, and frequency distributionperclass; andb) the interpretation ofmultiple regressionanalysis. Based on the analysis of the data collected from the government agencies, the results of the study indicated significant positive correlationbetween SISP practices and performance of the agencies.